Residual capacity of a reinforced concrete grillage deck exposed to corrosion. Issue 1 (2nd January 2020) - Conti, Elisa; Malerba, Pier Giorgio; Quagliaroli, Manuel; Scaperrotta, Diego
Abstract: Grillage decks made of reinforced concrete (RC) with more than 40–60 years of service life may exhibit localised areas of severe damage or even entire elements exceeding the serviceability limits. In these cases, it is essential to quickly and efficiently assess the structure's safety margins, and, in the worst cases, to also verify whether the damaged deck's residual bearing capacity is sufficient for it to be used as a platform for the repair works. This article proposes an assessment based on a non-linear RC finite element specialised in dealing with systems working in bending and torsion. The damage, measured at a particular time after construction, is modelled by a reduction of the reinforcement section, supposed to be induced by chlorides diffusion and investigated through a Cellular Automata algorithm. Such an approach is applied in studying a bridge deck, having an edge beam damaged by leakage of salted water from the road platform. The results give a thorough description of the structural behaviour and the deformed shapes help in understanding the redistribution process of the internal forces. These results may provide a reliable reference to plan proper maintenance actions as well as to establish a hierarchy of repairing and strengthening interventions.